Patterns of Clinical Reactivity in a Danish Cohort of Tree Nut Allergic Children, Adolescents, and Young Adults - Juel-Berg, Nanna; Larsen, Lau Fabricius; Küchen, Niels; Norgil, Ida; Hansen, Kirsten Skamstrup; Poulsen, Lars K. (Frontiers in Allergy, 2022)
Background Tree nut allergy is associated with severe reactions and poly-sensitization to other nuts and peanuts often occurs. There are regional differences in sensitization profiles that result in differences in clinical presentation. Denmark is located in a birch pollen endemic area, which could influence the allergy patterns due to pollen cross-sensitization. Objective This study aimed to investigate patterns of sensitization and clinical reactivity to tree nuts and peanuts and threshold levels for oral food challenges (OFCs) in a Danish cohort of tree nut allergic children, adolescents, and young adults. Methods Forty tree nut allergic subjects were assessed for clinical reactivity to six nuts, i.e., hazelnut, walnut, pistachio, cashew, almond, and peanut, by OFCs or convincing medical history of an immediate allergic reaction or tolerance. Clinical presentation and allergen-specific immunoglobulin E (sIgE) levels together with eliciting dose and rescue medication in OFCs were furthermore assessed. Results Allergy to two or more tree nuts was observed in most cases. Hazelnut-walnut dual allergy was common but not exclusively observed as concomitant allergies. Allergy to cashew was coincided in all but one of the assessed subjects with pistachio allergy. Half of all assessed subjects were allergic to peanuts. Oral symptoms followed by a skin reaction were the most common symptomatology that lead to OFC cessation and subjects often presented with symptoms from two or more organ systems. OFC threshold levels were within the same range, but cashew was distinguished from other nuts by causing allergic symptoms at the lowest dose. Clinical reactivity and the allergy patterns were to some extent reflected by sIgE levels and by correlations in sIgE between the nuts. Conclusions In this Northern European cohort, subjects with clinically relevant tree nut allergy were generally allergic to two or more tree nuts and close to half of them also to peanuts. There were two distinct and independent allergic phenotypes; the majority of hazelnut allergic subjects were also allergic to walnut, and all but one subject with cashew allergy were dual allergic to pistachio. These findings are consistent with a strong sIgE correlation between hazelnut and walnut and a close to total sIgE correlation between cashew and pistachio.